2019
DOI: 10.3389/fnins.2019.00456
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum S100B Levels in Patients With Epilepsy: A Systematic Review and Meta-Analysis Study

Abstract: Importance: Accumulating evidence suggests that serum levels of S100B may play a role in epilepsy. Objective: We performed a meta-analysis to quantitatively summarize the serum S100B data available for patients with epilepsy. Data source: Two independent researchers conducted a systematic investigation of the Harvard Hollis+, Open Gray, Clinicaltrials, Wanfangdata, and CNKI databases through Dec 6, 2018, for all studies published in English and Chinese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 37 publications
1
33
0
Order By: Relevance
“…Several investigators have demonstrated elevated brain injury marker levels in epilepsy, but there is not much data on levels in adults with new-onset seizures. Our results are well in line with previous studies of elevated S100B levels in epilepsy [25][26][27], which indicate that this marker should be investigated further for biomarker potential early in the disease course and perhaps as a marker of seizure burden. Pathophysiologically, increased levels of S100B could result from disruption of the blood brain barrier [14,28,29].…”
Section: Discussionsupporting
confidence: 91%
“…Several investigators have demonstrated elevated brain injury marker levels in epilepsy, but there is not much data on levels in adults with new-onset seizures. Our results are well in line with previous studies of elevated S100B levels in epilepsy [25][26][27], which indicate that this marker should be investigated further for biomarker potential early in the disease course and perhaps as a marker of seizure burden. Pathophysiologically, increased levels of S100B could result from disruption of the blood brain barrier [14,28,29].…”
Section: Discussionsupporting
confidence: 91%
“…Recently, Shekh-Ahmad [ 21 ] compared the total antioxidant capacity (TAC) in plasma, cortex, and hippocampus of an epilepsy mouse model, and they found decreased TAC levels in all districts, with comparable increases after antioxidant treatment, indicating that the biochemical changes occurring in SNC can be reflected in blood. Blood biomarkers as a surrogate for brain neurophysiology in epilepsy have also been analyzed by Liang et al [ 33 ], who found elevated levels of blood S100B at seizure onset and after seizures in patients. Although more studies will be needed to demonstrate if defects in the CNS can be translated into blood biomarkers fluctuations, by this study, we explore the possibility that ferroptosis biomarkers can be an index of patient’s disease status and, potentially, progression.…”
Section: Discussionmentioning
confidence: 99%
“…A first study ( 67 ) demonstrated that blood S100B is elevated at seizure onset and after seizures, in support of the hypothesis that BBB damage may trigger a seizure ( 7 , 101 103 ). A systematic review analyzed 18 studies and a total of 1,057 subjects, indicating that epileptic patients displayed elevated S100B blood levels as compared to controls ( 104 ). Meta-regression analyses showed that gender and mean age can impact serum S100B levels ( 104 ).…”
Section: Peripheral Biomarkers Of Bbb Permeability and Seizure Conditmentioning
confidence: 99%
“…A systematic review analyzed 18 studies and a total of 1,057 subjects, indicating that epileptic patients displayed elevated S100B blood levels as compared to controls ( 104 ). Meta-regression analyses showed that gender and mean age can impact serum S100B levels ( 104 ). Another study correlated MRI T1 peri-ictal imaging to blood S100B in drug-resistant epileptic patients, confirming the increase in BBB permeability during a seizure ( 105 ).…”
Section: Peripheral Biomarkers Of Bbb Permeability and Seizure Conditmentioning
confidence: 99%